2006
DOI: 10.1074/jbc.m605926200
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Key Intermediates in the Catalytic Cycle of Aspartate-β-semialdehyde Dehydrogenase from a Gram-positive Infectious Bacteria

Abstract: Aspartate-␤-semialdehyde dehydrogenase (ASADH) catalyzes a critical branch point transformation in amino acid biosynthesis. The products of the aspartate pathway are essential in microorganisms, and this entire pathway is absent in mammals, making this enzyme an attractive target for antibiotic development. The first structure of an ASADH from a Gram-positive bacterium, Streptococcus pneumoniae, has now been determined. The overall structure of the apoenzyme has a similar fold to those of the Gram-negative and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 25 publications
3
67
0
2
Order By: Relevance
“…In complete agreement with the structure of the ASD-aspartyl thioacyl adduct (22,31), the malonyl group is mainly anchored to the polypeptide via its carboxylate group by forming hydrogen bonds with the strictly conserved residues Gln 180 , Arg 241 , and His 248 (Fig. 4).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In complete agreement with the structure of the ASD-aspartyl thioacyl adduct (22,31), the malonyl group is mainly anchored to the polypeptide via its carboxylate group by forming hydrogen bonds with the strictly conserved residues Gln 180 , Arg 241 , and His 248 (Fig. 4).…”
supporting
confidence: 51%
“…3A), which resembles that found in the ASD-NADP ϩ and GAPDH-NADP ϩ -structures (22,23). NADP ϩ is positioned along the C-terminal side of the central ␤-sheet of the dinucleotide binding domain partly capped by the protruding cover loop that bridges strand 171:180 and 199:202 of the dimerization domain (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Hinge Bending; Comparison with Apo-and HoloKPR-Cofactor-induced hinge bending domain closure has been observed for several dehydrogenases, including alcohol dehydrogenase (34), formate dehydrogenase (35), glutamate dehydrogenase (36), diaminopimelate dehydrogenase (37), and aspartate-␤-semialdehyde dehydrogenase (38). It was, therefore, surprising that the crystal structure of the KPR⅐NADP ϩ complex compared with apoKPR revealed no evidence of a hinge bending induced by the cofactor (18).…”
Section: Resultsmentioning
confidence: 99%
“…5A). Interdomain movement upon the binding of NADP ϩ was reported in aspartate-␤-semialdehyde dehydrogenases (28,29); however, this was not the case for TtLysY. A comparison of the present TtLysY structure with the apo-TtLysYHB8 structure revealed that both structures were essentially the same (root mean square deviation ϭ 0.4 Å).…”
Section: Ttlysy Catalyzes the Nadph-dependent Reduction Ofmentioning
confidence: 79%